Blackness out of Place: Black Countervisuality in Portugal and Its Former Empire. - Marcos, Patrícia Martins (Radical History Review, 2022)
This article explores how historical narratives and aesthetic models configuring Portuguese imperial visuality produced the absented presence of Africa and its diasporas. Despite centuries of interconnected histories of colonial domination and enslavement, but also marronage and resistance, Black subjecthood was reduced in Portugal to a "foreign" presence. These silences ossify a regime of imperial visuality premised on the hegemonic overrepresentation of white masculinity—rendered through depictions of "navigators" as paragons of historical agency. Through the analytic countervisual quilombismo, this essay confronts such elisions by engaging with Achille Mbembe's Afropolitan call to "produce new images for thought." Focus on countervisual maroon (quilombismo) methods of refusal and fugitivity reveals the enactment of Black sovereignty and affirms Blackness as being. By affirming Black life and autonomy, diasporic artists, performers, and everyday people interrupt colonial frames, refusing the ethnographic reduction of Blackness to a body and its classificatory markers, thus revealing possibilities for different pasts, presents, and futures.